Philippine medical thesaurus on anatomy digestive system, embryonic structures and urogenital system in Iluko - Manzano, Mel Joseph D. (2014)
This study sought to come up with a medical thesaurus on terms relevant to the digestive system, embryonic structures, and urogenital system of the human body utilizing words from the Iluko language; their relationship among each other and the correct pronunciation of the translated terms.